Cost-effectiveness of same-admission versus interval cholecystectomy after mild gallstone pancreatitis in the PONCHO trial. Issue 12 (12th August 2016) - da Costa, D W; Dijksman, L M; Bouwense, S A; Schepers, N J; Besselink, M G; van Santvoort, H C; Boerma, D; Gooszen, H G; Dijkgraaf, M G W
Abstract: Background: Same-admission cholecystectomy is indicated after gallstone pancreatitis to reduce the risk of recurrent disease or other gallstone-related complications, but its impact on overall costs is unclear. This study analysed the cost-effectiveness of same-admission versus interval cholecystectomy after mild gallstone pancreatitis. Methods: In a multicentre RCT (Pancreatitis of biliary Origin: optimal timiNg of CHOlecystectomy; PONCHO) patients with mild gallstone pancreatitis were randomized before discharge to either cholecystectomy within 72 h (same-admission cholecystectomy) or cholecystectomy after 25–30 days (interval cholecystectomy). Healthcare use of all patients was recorded prospectively using clinical report forms. Unit costs of resources used were determined, and patients completed multiple Health and Labour Questionnaires to record pancreatitis-related absence from work. Cost-effectiveness analyses were performed from societal and healthcare perspectives, with the costs per readmission prevented as primary outcome with a time horizon of 6 months. Results: All 264 trial participants were included in the present analysis, 128 randomized to same-admission cholecystectomy and 136 to interval cholecystectomy. Same-admission cholecystectomy reduced the risk of acute readmission for recurrent gallstone-related complications from 16·9 to 4·7 per cent ( P = 0·002). Mean total costs from a societal perspective were €234 (95 per cent c.i. –1249 to 738) less per patient in the same-admission cholecystectomy group. Same-admission cholecystectomy was superior to interval cholecystectomy, with a societal incremental cost-effectiveness ratio of –€1918 to prevent one readmission for gallstone-related complications. Conclusion: In mild biliary pancreatitis, same-admission cholecystectomy was more effective and less costly than interval cholecystectomy. Abstract : Reduces overall costs